HUBUNGAN STATUS GIZI DENGAN PRODUKTIVITAS KERA PADA PEKERJA PEMETK TEH DI PT. SARANA MANDIRI MUKTI KABUPATEN KEPAHIANG TAHUN 2021 - Eka Fitry; Emy Yuliantimi; Miratul Haya (Jurnal Vokasi Keperawatan (JVK), 2021)
AbstractFrom a physiological point of view, productivity is a mental attitude that always tries and holds the view that the quality of life today is better than yesterday and tomorrow must be better than today. This attitude always encourages them not to feel satisfied with what they have achieved, but they always develop themselves and improve their work abilities. Meanwhile, work productivity is the ratio between the results achieved and the participation of a united time labor. A workforce with good nutrition will have a better work capacity and endurance, and vice versa, a workforce with poor nutrition and a heavy workload will interfere with work and accelerate fatigue.The purpose of this study was to determine the relationship between Nutritional Status and Work Productivity of Tea Picking Workers at PT. SaranaMandiriMukti, Kepahiang Regency. This type of analytic observational research with cross sectional design. Held on April 30 to May 6, 2021 at the PT. Sarana Mandiri Mukti Kepahiang Regency with a total population of 496 respondents. The tools used in this study were weighing scales to measure body weight, microtoas to measure height, and questionnaires and observations to measure work productivity.Based on the results of research on tea picker workers, there were 38 people with abnormal nutritional status, consisting of 28 people with a percentage of 45.9% fat, 10 people with a percentage of 16.3% thin, while 23 people with a normal nutritional status were 23 people with a percentage of 37.7. %. Those included in the productive category were 33 people (54.1%) and 28 people (45.9%) who were not productive. Based on the results of statistical tests using the Chi-square test, it was found that the relationship between nutritional status and work productivity was 0.031 (p <0 , 05).Workers are expected to maintain and maintain normal nutritional status to support work productivity for workers